Regulatory and Legislative Support of Management Decisions for Support of Regional Development - Popov, Mykola; Prykhodchenko, Liudmyla; Rovynskyy, Yuriy; Rovynska, Kateryna; Kozulina, Svitlana (International Journal of Criminology and Sociology, 2021)
The article is devoted to certain aspects of normative-legal regulation of regional development. In the conditions of transformation processes, transition to the European integration vector of development, change of the system of regional management by means of reform of decentralization there is a question of maintenance of effective development of regions. Adoption and implementation of management decisions is a key factor in ensuring harmonious sustainable development. In the absence of a clear comprehensive structure of distribution of powers between authorities at different levels, there are problematic aspects of providing information and analytical support for management decisions. The interaction of different branches of government and authorities at different levels is inefficient. The basis for establishing an effective management system at the regional level is the development of a regulatory framework that would ensure a clear division of responsibilities and powers of the authorities to address certain socio-economic, social, environmental and other issues inherent in the level of regional development. Compliance of the regulatory framework with today’s requirements, the changes and transformations taking place in the country, world practices and international regulations is a priority to ensure effective decision-making and implementation of management decisions to create opportunities for regional development. The article analyzes the structure of management decisions at the regional level, taking into account the transformation processes in the system of regional governance associated with decentralization reform. The article develops ways to improve the development management system at the regional level.